DV and the Animateur Cinema in China - Voci, Paola (DV-Made China: Digital Subjects and Social Transformations after Independent Film, 2015)
Film scholarship on the movie-making, movie-viewing, and movie-circulating practices that have developed since the mid-1990s in China has appropriately emphasized the role played by the rise of digital video (DV) and its impact on independent and, in particular, documentary filmmaking. In this chapter, I want to explore one line of development in DV independent production that has received much less attention—what I call animateur cinema—which concerns short digital animations that are made by and/or circulated for online (or on-mobile) moviemakers/viewers. Fan-originated digital animation or egao animation can also be found online, but my focus is on animateur cinema
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé